Analysis of Import Duty Policy On the Protection of the Local Industry Sector: (Cross-Country E-Commerce Case Study) - Luthfi Annashrul, Fajar; Arnanda Arnanda; Salsa Abrilia, Rista; Novalita Aurelia, Vanessa (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2024)
The analysis of import duty policies on the protection of the local industry sector, especially in the context of cross-border e-commerce, has become very relevant amid the rapid development of digital trade. This study aims to evaluate the impact of import duty policies implemented by the Indonesian government on local industries and Micro, Small and Medium Enterprises (MSMEs). With increasing access to imported goods through e-commerce platforms, the challenges for local products are growing. New policies that regulate the amount of import duties, including the possibility of high tariffs, are expected to suppress the inflow of foreign goods that can harm domestic industries. Through this case study, it is hoped that an effective solution can be found to create a balance between the protection of local industries and ease of access for consumers in the digital era. The findings of this study are expected to provide better policy recommendations to support the growth of the domestic industrial sector.